Fusariums of the potato in Finland : 6. Varietal tuber resistance to Fusarium species - Seppänen, Esko (Annales agriculturae Fenniae, 1983)
Selostus: Perunalajikkeiden varastotautien kestävyys.
Keywords: peruna : varastotaudit; kasvitaudit : fusarium; resistenssi : peruna